Implementasi Metode Muhadatsah dengan Permainan Sifis Shuroh untuk Meningkatkan Keterampilan Maharah Kalam Siswa - Muzamil R Pawi; Ahmad Nur Mizan; Zulhannan (Cipta Media Harmoni, 2025)
The background of this study is the low speaking ability (maharah kalam) of grade VIII students. Observations show that educators continue to use the lecture method in the Arabic language learning process which results in less than optimal student learning outcomes. The purpose of this study is to improve students' speaking ability by applying the Muhadatsah method with the Sifis Shuroh game. The research method is Classroom Action Research (CAR) with the Hopkins model. The research activities were carried out in two cycles, where each cycle includes the planning, implementation, observation, and reflection stages. Data were collected using a quantitative approach through calculating student grades and qualitatively through interviews, observations, and documentation data. The results of the study showed an increase in students' maharah kalam skills. At the pre-research stage, only 9 out of 32 students (28%) completed it, while 23 students (72%) had not completed it. After cycle I, the number of students who completed it increased to 14 people (43.75%), while those who had not completed it were 18 people (56.25%). A more significant increase occurred in cycle II, where 23 students (71.75%) managed to achieve completion, and only 9 students (28.25%) had not completed it. Thus, it can be concluded that the application of the Muhadatsah method through the Sifis Shuroh game.